Abschätzung nach unten der Zahl der Lösungen der Gleichungen vom Typ Hardy—Littlewood in Sektoren - Poljanskij, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. А. Полянский. Оценка числа решений уравнений типа Гарди—Литтлвуда в секторах A. Poljanskis, Hardi—Litlvudo tipo lygčių sprendinių skaičiaus sektoriuose įvertinimas